2005
DOI: 10.1300/j083v45n04_05
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Positive Well-Being of Grandparents Caring for Their Grandchildren

Abstract: Prior research on grandparent caregivers has focused on stress, depression, and other negative outcomes. This paper describes research on factors that are associated with grandparents' positive well-being. In particular, it investigated the extent to which the perception of grandparental stress and grandparents' resources are associated with grandparents' well-being, after controlling for sociodemographic and health factors. A sample of 129 grandparents had individual interviews. Using a hierarchical block mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 26 publications
0
28
0
3
Order By: Relevance
“…Erikson y Kivnick denominaron este aspecto como una "segunda oportunidad en la generatividad" y fue planteado también en la teoría de la continuidad (15). Otro factor positivo para los abuelos cuidadores es que puede modificar en ellos algunas conductas inapropiadas y puede intervenir en adquirir comportamientos saludables como dejar de fumar o beber por la responsabilidad que sienten de dar un buen ejemplo y de mostrar estilos de vida saludables (23), además pueden hacer sentir a estos adultos mayores que su red de apoyo aumenta al contar con su nieto.…”
Section: Implicaciones Para El Adulto Mayorunclassified
See 1 more Smart Citation
“…Erikson y Kivnick denominaron este aspecto como una "segunda oportunidad en la generatividad" y fue planteado también en la teoría de la continuidad (15). Otro factor positivo para los abuelos cuidadores es que puede modificar en ellos algunas conductas inapropiadas y puede intervenir en adquirir comportamientos saludables como dejar de fumar o beber por la responsabilidad que sienten de dar un buen ejemplo y de mostrar estilos de vida saludables (23), además pueden hacer sentir a estos adultos mayores que su red de apoyo aumenta al contar con su nieto.…”
Section: Implicaciones Para El Adulto Mayorunclassified
“…En ocasiones los abuelos pueden funcionar como negociadores entre nieto y padre disminuyendo las tensiones que se pueden generar entre ellos (15). Otro aspecto importante en esta relación es la transmisión de la cultura a partir de prácticas realizadas por el adulto mayor, juegos, música y costumbres que el niño conoce mediante el cuidado (doble dependencia).…”
Section: Beneficios De Las Relaciones Intergeneracionalesunclassified
“…Our friends are changing (Landry-Meyer & Newman, 2006). Sands et al (2005) found a correlation between grandparents' perception of stress and their actual well-being. They suggest that grandparents can be helped through supportive, strengths-based individual, or family counseling which can assist them in reframing their situation positively and by enhancing the "resilience that is within their families, such as a sense of cohesion, financial stability, a sense of mastery, and communication" (p. 78).…”
Section: Need For Access To Counseling/support Groupsmentioning
confidence: 87%
“…In a study of predictors of grandparent carers' health status, Leder, Grinstead, and Torres (2007) found that grandparents reported considerable benefit from the emotional support they received from support groups and from their sense that someone else was in a similar situation as them. Meanwhile, Sands et al (2005) reported a negative correlation between support groups and grandparent well-being. It's been suggested that in order for a support group to be effective, there must be a balance between having members vent and having them receive new information -a lack of balance in this area could increase the anxiety of the participants and impact the effectiveness of the support group.…”
Section: Need For Access To Counseling/support Groupsmentioning
confidence: 99%
See 1 more Smart Citation